Analysis of the genetic diversity and population structure of Perinereis aibuhitensis in China using TRAP and AFLP markers. (April 2015) - Liu, Fei; Shi, Hong-Zhuan; Guo, Qiao-Sheng; Lv, Fu; Yu, Ye-Bing; Lv, Lin-Lan; Shen, Wen-Biao; Zhao, Wei-Hong; Zhang, Ming-Ming
Abstract: Perinereis aibuhitensis is found in the coastal waters of northwestern Pacific. Different ecotypes are distributed throughout the coastal sea beach based on their ecology and behavior, but relatively little is known about the population structure of this species. In this study, we estimated the genetic relationships within P . aibuhitensis using Target Region Amplified Polymorphisms (TRAP) and Amplified Fragment Length Polymorphisms (AFLP) that were derived from related populations on the coasts of China. All populations were uniquely fingerprinted using the TRAP and AFLP marker method. The mean genetic distance was estimated to be 0.1859 based on the TRAPs and AFLPs. Using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) by Molecular Evolutionary Genetics Analysis (MEGA) 6.06 software, Principal Coordinate Analysis (PCA) and STRUCTURE analysis, the phylogenetic tree of the ten P . aibuhitensis populations was separated into four major clusters; however, the mantel test indicated that there was no signiﬁcant correlation between the genetic and geographical distances due to gene differentiation and gene flow (P > 0.005). The genetic diversity was low for P . aibuhitensis at the population level compared with the species level. Finally, an appropriate strategy for conserving the P . aibuhitensis germplasm is proposed. Highlights: We assayed the population genetics of Perinereis aibuhitensis using TRAR and AFLP markers. The phylogenetic tree of the ten P . aibuhitensis populations was separated into four major clusters. The genetic diversity was low for P . aibuhitensis at population level when comparing with that at species level. Finally, an appropriate strategy for conserving the P . aibuhitensis germplasm is proposed.